Influence of cataract surgery in biopsychosocial adaptation in the elderly - Leonor Rosario Diaz Alfonso; Elvira Machado Héctor; Bárbara Suárez Rodríguez; Mariela Julia Curbelo Gómez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2010)
Background: The twenty-first century is characterized by a progressive aging in the population, with the subsequent demand of medical care it implies due to the polimorbility rates typical of this stage of life. Objective: to prove the positive influence of cataract surgery in biopsychosocial adaptation of elderlies. Methods: a descriptive study conducted from January to June 2008 in the General University Hospital "Dr. Aldereguía Gustavo Lima'' in Cienfuegos. The 60 elder patients who underwent surgery cataract in that period were included. Geriatric evaluation was used as assessment instrument. It was applied before and 3 months after cataract surgery and included the Yesavage Geriatric Depression Rating Scale to measure emotional function and the Katz index for functional evaluation. The variables used are part of the preoperative geriatric assessment. Among them we can find biomedical, social, functional and psychological aspects as well as-risk benefit and anesthetic risks analysis. Results: the largest amount of patients was between 70 and 74 years old, predominantly males and white skinned. Most frequent personal pathological records were arthropathies, diabetes mellitus and hypertension. A significant relationship between initial visual acuity levels and depression rates was found; as well as limitations in performing basic daily life activities. Conclusions: with surgical intervention an improved visual acuity was achieved and a number of functional capacities were reestablished to allow a better biopsychosocial adaptation in elderlies.